SACRED NARRATIVES UNVEILED: EXPLORING THE SYMBOLISM OF LINTANG GOWANG IN WAYANG KAMASAN PAINTINGS AT BALE KAMBANG TAMAN GILI KERTHA GOSA - I Wayan Agus Eka Cahyadi; I Wayan Adnyana; I Wayan Mudra; I Putu Udiyana Wasista; I Wayan Swandi (CV. RADJA PUBLIKA, 2024)
This study addresses the need for more documentation systematically analyzing the significance of wayang kamasan illustrations in Bale Kambang Taman Gili Kertha Gosa. Despite historical actors passing away and lacking comprehensive studies on these illustrations, the article examines the iconographic meaning of lintang gowang. Researchers are intrigued by this phenomenon, especially considering the absence of empirical evidence supporting the conscious self-beheading capacity, a crucial aspect from a medical perspective. The incorporation of limb offerings and blood rituals in Hinduism strengthens the motivation to explore the illustration's meaning, particularly in evolving offering traditions in Bali. This visual narrative holds distinct significance, requiring extensive scholarly inquiry. Using an iconographic approach, qualitative research reveals narrative motifs in Tantri Kamandaka stories and tantra yana teachings involving head offerings, symbolizing a surrender act reaching the pinnacle of consciousness. The dramatized beheading and voluntary surrender underscore the doctrinal essence of self-offering, transcending dualities and the human ego, aiming for the highest consciousness levels.